2019
DOI: 10.1186/s12879-019-4315-6
|View full text |Cite|
|
Sign up to set email alerts
|

HCV-infected individuals have higher prevalence of comorbidity and multimorbidity: a retrospective cohort study

Abstract: Background: Almost 1% of Canadians are hepatitis C (HCV)-infected. The liver-specific complications of HCV are established but the extra-hepatic comorbidity, multimorbidity, and its relationship with HCV treatment, is less well known. We describe the morbidity burden for people with HCV and the relationship between multimorbidity and HCV treatment uptake and cure in the pre-and post-direct acting antiviral (DAA) era. Methods: We linked adults with HCV at The Ottawa Hospital Viral Hepatitis Program as of April … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 75 publications
2
9
1
1
Order By: Relevance
“…Therefore, there is a need for clinical trials to evaluate the efficacy and tolerance of the direct-acting antiviral agents for the treatment of HCV-associated renal diseases. In the present study, we found a comparatively low prevalence of HCV in COPD patients compared to previous studies worldwide (25,26). The reports on the association between HCV infection and COPD are exiguous.…”
Section: Discussioncontrasting
confidence: 61%
“…Therefore, there is a need for clinical trials to evaluate the efficacy and tolerance of the direct-acting antiviral agents for the treatment of HCV-associated renal diseases. In the present study, we found a comparatively low prevalence of HCV in COPD patients compared to previous studies worldwide (25,26). The reports on the association between HCV infection and COPD are exiguous.…”
Section: Discussioncontrasting
confidence: 61%
“…Распространенность коморбидной патологии в нашем исследовании выявлена у 63% пациентов с ХГС, также в 1/2 случаев имела место мультиморбидность. В ряде научных наблюдений отмечается более высокая распространенность как коморбидности, так и мультиморбидности у пациентов с ХГС в сравнении с общей популяцией [7,8]. Существует много сообщений о более высокой летальности у пациентов с ХГС при наличии различной сопутствующей патологии [9,10].…”
Section: Discussionunclassified
“…It was reported that, besides liver fibrosis and cirrhosis, extra-hepatic comorbidities including malignancies, cardiovascular diseases, CKD, and neurological diseases were well established in HCV-infected population [ 32 ]. Chronic viral infection, including HIV and HCV, induced to generate systemic chronic inflammation, which was more prone to cause serious noncirrhotic liver diseases (NCDs) via some mechanisms including oxidative stress and mitochondrial dysfunction [ 33 ].…”
Section: Discussionmentioning
confidence: 99%